AB0359 Treatment Effectiveness for Rheumatoid Arthritis after Switching from A Tumor Necrosis Factor Inhibitor to Another Agent. (15th July 2016) - Bonafede, M.; Curtis, J.R.; McMorrow, D.; Mahajan, P.; Chen, C.
Abstract : Background: When tumor necrosis factor inhibitor (TNFi) therapy fails in rheumatoid arthritis (RA), a majority of patients switch to another TNFi instead of a non-TNFi biologic disease-modifying antirheumatic drug (bDMARD). 1 The effectiveness of TNFi cycling compared with switching to a non-TNFi agent is not well established. Objectives: This study examined treatment effectiveness among patients with RA in a large, commercially insured population who cycled to another TNFi ("TNFi cyclers") compared with those who switched to a non-TNFi agent ("non-TNFi switchers"). Methods: Administrative claims from January 2010 to September 2014 were analyzed from the Truven Health MarketScan Commercial database. Eligible patients received a TNFi in the 12 months before the "index" drug (a different TNFi or non-TNFi [bDMARDs or tofacitinib]). The study included adults ages 18 to 64 years with ≥12 months of continuous medical and pharmacy enrollment pre- and post-index, and ≥1 claim for RA (ICD-9-CM 714.0x) pre-index or 30 days post-index with no other autoimmune condition. Treatment effectiveness was defined using a validated algorithm 2 that was applied to medical and pharmacy claims for 12 months post-index for each patient. Treatment was considered to be effective if the patient satisfied all 6 algorithm criteria in this period: (1) ≥80% adherence (subcutaneous medication possession ratio or number of intravenous infusions); (2) no increase in dose; (3) no switch to another bDMARD; (4) no new conventional DMARD; (5) no new/increased oral glucocorticoid; and (6) less than 2 glucocorticoid injections in the first 90 days after the index date. Logistic regression was used to compare effectiveness rates by treatment cohort, controlling for baseline demographic and clinical characteristics, including number of prior biologic therapies. Results: Of the 6, 945 patients who switched from a pre-index TNFi, 5, 020 (72.3%) were TNFi cyclers and 1, 925 (27.7%) were non-TNFi switchers. Achievement rates for all 6 algorithm criteria combined and for individual criteria in the 12 months post-index are shown in the table. In the logistic regression model, non-TNFi switchers were 1.25 times as likely as TNFi cyclers to achieve all algorithm criteria for effectiveness (odds ratio, 1.248; 95% CI, 1.103–1.414; P <0.001). Conclusions: On the basis of a claims-based algorithm of treatment effectiveness for RA, it appears that patients who switch from TNFi to non-TNFi agents are more likely to achieve treatment effectiveness criteria for 12 months after switching than patients who cycle to another TNFi. References: Bonafede M et al. Adv Ther. 2012;29:664–674. Curtis JR, et al. Arthritis Res Ther. 2011;13:R155. Acknowledgement: This study was sponsored by Sanofi and Regeneron Pharmaceuticals, Inc. Jonathan Latham assisted with preparation and submission of the abstract. Disclosure of Interest: M. Bonafede Employee of: Truven Health, which was awarded a research contract from Sanofi and Regeneron Pharmaceuticals for this work, J. Curtis Consultant for: Sanofi and Regeneron Pharmaceuticals, Inc., D. McMorrow Employee of: Truven Health, which was awarded a research contract from Sanofi and Regeneron Pharmaceuticals for this work, P. Mahajan Shareholder of: Sanofi, Employee of: Sanofi, C. Chen Shareholder of: Regeneron Pharmaceuticals, Inc., Employee of: Regeneron Pharmaceuticals, Inc.